Elites and people : challenges to democracy - Engelstad, Fredrik, 1944-; Gulbrandsen, Trygve; Mangset, Marte; Teigen, Mari (Comparative Social Research Ser., 2019)
The present volume of Comparative Social Researchoffers a broad set of comparative studies of elites, stretching from the Arab Spring in Tunisia and Egypt to women's political leadership in Brazil and Germany, via attainment of elite positions among minorities in France and the US.